2018
DOI: 10.1186/s40621-018-0148-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a proactive health and safety risk management system in the fire service

Abstract: BackgroundThis study evaluated the efficacy of a fire department proactive risk management program aimed at reducing firefighter injuries and their associated costs.MethodsInjury data were collected for the intervention fire department and a contemporary control department. Workers’ compensation claim frequency and costs were analyzed for the intervention fire department only. Total, exercise, patient transport, and fireground operations injury rates were calculated for both fire departments.ResultsThere was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…A prospective study found a sleep health program resulted in significantly fewer reported injuries among FFs 110 . A proactive risk management program intervention among FFs reduced injuries, and workers' compensation claims and costs, but did not result in significant changes in injury rates 99 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A prospective study found a sleep health program resulted in significantly fewer reported injuries among FFs 110 . A proactive risk management program intervention among FFs reduced injuries, and workers' compensation claims and costs, but did not result in significant changes in injury rates 99 …”
Section: Resultsmentioning
confidence: 99%
“…110 A proactive risk management program intervention among FFs reduced injuries, and workers' compensation claims and costs, but did not result in significant changes in injury rates. 99…”
Section: Injurymentioning
confidence: 99%
“…The findings of this study suggest that WLFFs appreciate and use risk mitigation strategies implemented by their organization and the USDA, such as equipment trainings, daily physical therapy, personal protective equipment, and policies and procedures. Risk mitigation strategies implemented in fire departments typically result in an increase in overall health, wellness, and safety 38,39 . This study identified that the use of such risk mitigation strategies gave WLFFs confidence in their ability to do their jobs.…”
Section: Discussionmentioning
confidence: 98%
“…Risk mitigation strategies implemented in fire departments typically result in an increase in overall health, wellness, and safety. 38,39 This study identified that the use of such risk mitigation strategies gave WLFFs confidence in their ability to do their jobs. Furthermore, onboarding training and required safety certifications contributed to participants' confidence in risk mitigation strategies.…”
Section: Risk Mitigation Strategiesmentioning
confidence: 99%
“…Firefighters routinely engage in duties that expose them to a range of safety and health risks [1][2][3]. Firefighting and emergency medical response are especially physically demanding work activities, requiring frequent lifting, pushing, and pulling of heavy loads that place firefighters at an increased risk for work-related musculoskeletal disorders [1,4,5]. Such work is often performed wearing heavy gear and equipment and in work environments that further aggravate the risk for injury.…”
Section: Introductionmentioning
confidence: 99%